An Overview of the Evolution of Security and Stability of China’s Power System - Wu DONG; Jian ZHANG; Qinyong ZHOU; Libo ZHANG; Haoyue GONG (Zhongguo dianli)
In order to take measures in advance to prevent the decline of the safety and stability level of the power system, it is necessary to clarify the impact of the new energy revolution on the evolution of the security and stability of China's power system. According to the scale and growth of the power grid in the process of China's power system development, the security and stability of China's power system is divided into four stages of development. The typical instability problems of the power system at different stages are summarized. The dominant factors affecting the security and stability of the power system at each stage are analyzed, and the mechanisms and causes for the conversion of security and stability are clarified. It is pointed out that under the new energy revolution, the security and stability of the power system appears decoupling from the scale of the power system. Proposals are made to construct a power grid evolution model and establish a comprehensive assessment indexes of stability level to quantify and predict the trend of future changes in the security and stability level of the power system.